Magnetic Resonance Imaging Findings In Patients Above 40 Years of Age, With Neck Pain: MRI Findings in Patients above 40 Years of Age with Neck Pain - Yaqoob, Sehrish; Zakir, Muhammad; Yousaf, Imran; Farooq, Syed Muhammad Yousaf; Fatima, Mehreen; Ahsan, Zahra; Delawar, Sana; Tooba, Sarwat Jabeen; Zaman, Aneela; Rehman, Khaleel-Ul (Pakistan BioMedical Journal, 2022)
Neck pain considerably influences worldwide. Neck pain is a common finding of the cervical spine abnormality. Disc degeneration is associated with progressive age groups. Objective: To find the Magnetic Resonance Imaging findings in patients above 40 years of age, with neck pain. Methods: In Shalamar Hospital Lahore, a descriptive study was conducted on MRI Philips MULTIVA 1.5 Tesla. 200 patients of above 40 years age groups were enrolled in this study with convenient sampling technique. All patients referred by clinicians with neck pain. Both male and female were included. Prior Neck Surgery, Traumatic Spine Fractures, Metabolic Bone Disease Spinal Infection, Rheumatoid Arthritis, Active Malignancy, prosthesis inside the body or any contra-indication to MRI were excluded. Results: Among 200 patients of different age groups, MRI findings were noted that reduced vertebral height, disc height, signal changes T2 and disc bulge present in patient with neck pain. 1 male patient had reduced vertebral height at C6 (0.5%) in 40-60 age group. 105 patients (52.7% males) had reduced disc height at C5/C6 (45.8%) in 81-100 age group and six patients had reduced signal intensity T2 at C6/C7 (3%) in 81-100 age group most frequently in males. 57 patients (34.4% females) of 40-60 age group had reduced disc bulge at C5/C6 (22.4%) level. Conclusion: Signal intensity T2 of the intervertebral disc and disc height were reduced in eighty-one to hundred age group and others findings were reduced at forty to sixty age groups i.e., vertebral height and disc bulge.